Efficacy and safety of berberine on the components of metabolic syndrome: a systematic review and meta-analysis of randomized placebo-controlled trials - Liu, Dangzhen; Zhao, Haiyan; Zhang, Yiwen; Hu, Jingqing; Xu, Hong (Frontiers in Pharmacology, 2025)
BackgroundMetabolic syndrome (MetS) is a prevalent metabolic disease that significantly increases the risk of type 2 diabetes, cardiovascular diseases, and overall mortality. Current medications have limited effects on the various components of MetS. Berberine has demonstrated unique comprehensive therapeutic benefits for MetS, but its efficacy remains uncertain.ObjectiveTo comprehensively evaluate the efficacy and safety of berberine on MetS indicators.MethodsOur study provides a comprehensive evaluation of the efficacy and safety of berberine for MetS components through systematic review and meta-analysis, from the aspects of study characteristics, risk of bias, meta-analysis, sensitivity analysis, meta-regression, and publication bias.ResultsThe results indicate that berberine significantly reduces triglycerides (TG) (WMD: −0.367 mmol/L; 95% CI: −0.560 to −0.175; p < 0.001), fasting plasma glucose (FPG) (WMD: −0.515 mmol/L; 95% CI: −0.847 to −0.183; p = 0.002), and waist circumference (WC) (WMD: −3.270 cm; 95% CI: −4.818 to −1.722; p < 0.001) among the components of MetS, but has no significant effect on high-density lipoprotein cholesterol (HDL-C), systolic blood pressure (SBP), or diastolic blood pressure (DBP). Additionally, berberine also improves the secondary indicators of low-density lipoprotein cholesterol (LDL-C) (WMD: −0.495 mmol/L; 95% CI: −0.714 to −0.276; p < 0.001), total cholesterol (TC) (WMD: −0.451 mmol/L; 95% CI: −0.631 to −0.271; p < 0.001), body mass index (BMI) (WMD: −0.435 kg/m2; 95% CI: −0.856 to −0.013; p = 0.043), and 2-h oral glucose tolerance (2hOGTT) (WMD: −1.606 mmol/L; 95% CI: −1.891 to −1.321; p < 0.001). Meta-regression and subgroup analyses indicate that short-term treatment (≤90 days) is more effective for HDL-C and LDL-C than long-term treatment. Regarding safety, no significant difference was observed between berberine and placebo.ConclusionBerberine significantly improves glucose and lipid metabolism and has notable effects on components of MetS, including TG, FPG, and WC, with a favorable safety profile. It may serve as a beneficial supplement. Meanwhile, more high-quality, rigorously designed randomized controlled trials are needed in the future to provide stronger evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024588614.